2012
DOI: 10.1155/2012/167062
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal Barriers to Analgesic Use among Patients with Substance Use Disorders

Abstract: Attitudinal barriers towards analgesic use among primary care patients with chronic pain and substance use disorders (SUDs) are not well understood. We evaluated the prevalence of moderate to significant attitudinal barriers to analgesic use among 597 primary care patients with chronic pain and current analgesic use with 3 subscales from the Barriers Questionaire II: concern about side effects, fear of addiction, and worry about reporting pain to physicians. Concern about side effects was a greater barrier for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…It is important to note that many of the patients who wanted more priority placed on discussing pain, as well as those who expressed desire for their pain to be recognized as real, were not seeking to discuss opioids; many were in fact avoiding opioids and looking for a sympathetic ear, while others wanted answers to questions about the origins and implications of their pain symptoms. Indeed, prior research has demonstrated that especially for patients with substance abuse disorders, concerns about addiction and side effects can be barriers to the use of opioid therapy . If PCPs conclude that those patients who want to discuss pain necessarily want to discuss opioids, there may be a tendency for conversations about pain to be approached more hesitantly or even delayed until the patient–provider relationship is perceived as more well defined.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that many of the patients who wanted more priority placed on discussing pain, as well as those who expressed desire for their pain to be recognized as real, were not seeking to discuss opioids; many were in fact avoiding opioids and looking for a sympathetic ear, while others wanted answers to questions about the origins and implications of their pain symptoms. Indeed, prior research has demonstrated that especially for patients with substance abuse disorders, concerns about addiction and side effects can be barriers to the use of opioid therapy . If PCPs conclude that those patients who want to discuss pain necessarily want to discuss opioids, there may be a tendency for conversations about pain to be approached more hesitantly or even delayed until the patient–provider relationship is perceived as more well defined.…”
Section: Discussionmentioning
confidence: 99%
“…51 Meanwhile, patients with co-occurring pain and addiction may be wary of accurately reporting their pain and addiction behaviors, especially if they believe their clinician will discontinue their opioid prescription or engage in stigmatizing behaviors. 10,60,106…”
Section: Intersecting Stigmasmentioning
confidence: 99%
“…Rampant polypharmacy, coupled with lack of awareness, has had a huge impact on analgesic efficacy and presents tolerability issues 40. Several misconceptions regarding use of analgesics and fear of adverse events associated with the use of opioids or surgical methods of analgesia result in suboptimal treatment of pain 41,42. These inadequacies might be overcome by the amalgamation of expert opinions and available evidence to form standardized treatment guidelines for pain therapy.…”
Section: Unmet Needs Of Indiamentioning
confidence: 99%
“… 40 Several misconceptions regarding use of analgesics and fear of adverse events associated with the use of opioids or surgical methods of analgesia result in suboptimal treatment of pain. 41 , 42 These inadequacies might be overcome by the amalgamation of expert opinions and available evidence to form standardized treatment guidelines for pain therapy. Hence, an expert panel was convened to delve on these lacunae and frame an appropriate treatment paradigm for pain management.…”
Section: Unmet Needs Of Indiamentioning
confidence: 99%